Medical ethics and practices from Islamic perspective - Gul, Khanda; Gul, Palwasha; Gul, Pari; Azeem, Seema (International Journal Of Community Medicine And Public Health, 2020)
Ethical physicians seem to have become an uncommon entity in modern day medical practice. Many patients and physicians feel that the profession of medicine is not living up to its own standards and expectations. One of the reasons is the lack of knowledge of the medial professionals about their religion and medical ethics. The ethics is not being right or wrong, instead it is the process of making better decisions or worse decisions compared to the worst decision. The introduction of newer technology in medical field such as organ transplantation, biotechnical parenting, blood transfusion, surrogacy, gender identification on fetal ultrasound, female genital mutilation has posed Muslim physicians and patients with some new questions of ethics. We look upon issues from the perspective of Muslim doctors and it is therefore important to discuss few of the practices according Quran, Sunnah. If the answers are not given in Quran and sunnah then one may turn to Ijma.